O canto coral na formação de atores: processos, princípios e procedimentos - Lucile Cortez Horn (2014)
In this study we identified the processes, principles and procedures that guide the development of specific pedagogical strategies directed to the choir practice, which becomes a privileged instrument to the actor formation. This question emerged during our career, where we developed methodologies that facilitate the musicalization of non musicians. Considering that most actors in Brazil have none musical formation, we seek to identify the contributions that the musicalizationthrough this practice may bring to the actor in formation. Therefore, this thesis aims to present processes, principles and procedures that guide the musicalization of the actor through choir practice. To achieve this objective, we performed a bibliographic review, based on the critical-analytical lecture of the thinking and the pedagogicalartisticpractice of authors-researchers that discuss the importance of musicalparameters appropriation by the actors in their formation processes, adjusted to the theatrical characteristics and in the critical analysis of the strategies developed and applied in our artistic and pedagogical acting, based on the thinking and practice of the authors that fundament this thesis. In referencing the research in the authors work, we included musical records and scores in the scenic arts course, where the author acted, and testimonials of students from this course collected in collective interviews performed by the author. In these interviews, the students assert that the choir practice contributed to their formation as well as to their acting. We highlight among the identified principles, the motivation, the dialectic collectivity/individuality,the playfulness, the movement-singing relation, among others. Among the processes, we highlight the development of musical perception, the appropriation ofmusical elements, the situated learning. As for procedures, we stress the repetition, imitation, the auditory training, the respiratory exercises, displacements in space and the creation of musical arrangements specific for the vocal/choir group in question.